Rescuing the Perishing Heathen: The British Empire versus the Empire of Satan in Anglican theology, 1701–1721 - Strong, Rowan (Studies in church history, 2009)
In 1493-94, Pope Alexander VI divided the globe between Spain and Portugal with reference to their conquest of the territories of the New World. In the eighteenth century, Anglicans divided the globe into the territory of Christ and the lands and peoples under the dominion of Satan. The Bishop of Carlisle in 1719 was adamant that that indigenous heathen peoples were ‘insensible of the great Concernments of their immortal Souls, and very much uncertain, at best, in their apprehensions of a future life; they are abandoned to their lusts and passions; and under the dominion of Satan’. Consequently, affirmed Edward Waddington of Eton College in 1720, Satan was alarmed by the formation of a new Anglican mission society for work in British North American and West Indian colonies ‘at the approaching Loss of so many Millions of Subjects’. Through heathen ignorance of their spiritual captivity the Devil ‘supported an Empire of almost equal extent with the Universe, and led the World captive at his pleasure’, except where Christ had delivered humankind from devilish tyranny and dominion.